PERBEDAAN HASIL BELAJAR MENGGUNAKAN MEDIA POWER POINT DENGAN MEDIA KONVENSIONAL PADA MATERI SENI RUPA DI SMAN 1 SUNGAI TARAB TANAH DATAR - NINDRI GUSTIA, Drs. Eswendi,M.Pd, Dra. Jupriani, M.Sn (Serupa The Journal of Art Education, 2014)
can not improve student learning outcomes to the fullest. This study aims to determine whether there are differences in learning outcomes using media power point with conventional media? This research includes the experimental research, the study population are students of SMAN 1 Tarab River Plains. The sample in this study was a class IX student of the school year 2013/2014 consisting of 2 classes, the experimental class and the control class. Class IX science class experiment 2 while the control class IX IPA 1 the number of students consisting of 40 people. Processing data using SPSS version 16. Analysis using t-tests on the experimental class and the control class. With an average test result of learning, tests of normality, homogeneity and hypotheses. The results of the study addressed that there are differences in learning outcomes of students in learning activities of media power point with conventional media in SMAN 1 TarabRiver Plains.Kata Kunci : hasil belajar, materi seni rupa, media power point